INVESTIGAÇÃO DAS MUDANÇAS REALIZADAS POR CONSTRUTORAS PARA ADAPTAÇÃO À NORMA DE DESEMPENHO NA CONCEPÇÃO DE EMPREENDIMENTOS - Santos, Paulo Ricardo Ramos; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The performance standard, NBR 15.575, constitutes a divisive landmark in Brazilian civil construction by introducing the concept of performance in an environment with prescriptive standards. Thus, its potential impact on the design of residential buildings is relevant. This reinforces the importance of studies investigating how agents involved in building construction are acting in this new scenario. Thus, this paper investigated the changes promoted by construction companies, with focus on the phases of planning, design and implementation of projects, to adaption of the performance standard. The research was carried out from a multiple case studies, with descriptive features. The data were collected from structured interviews with representatives of 16 construction companies from Aracaju, Sergipe. The results showed that the project phase gained more attention of the builders. There is a concentration of efforts for improvements in the compatibility and detailing of projects, for example. However, this commitment can be mitigated by the lack of importance required, which should be attributed to the other phases of an enterprise.